Experimental Analysis of Temperature Effect on a Typical Perovskite Silicon (Si) Tandem Solar Cell - Md Maroof Md Nayeem, Hamesh Babu Nanvala (Mathematical Statistician and Engineering Applications, 2022)
Solar energy is the most plentiful source of renewable energy on the globe; nevertheless, the potential of solar cells now available on the market has not been fully tapped in an effective manner. Either raising the efficiency of a solar cell or lowering its price would help make solar energy more affordable. This may be accomplished in a number of ways. The purpose of this thesis is to provide numerous strategies for increasing the efficiency of solar systems by meticulous design. These strategies make use of software that is already on the market, namely SETFOS and SCAPS-1D. These methods make an effort to enhance several aspects of solar cells, including their current, voltage, capacity to absorb light, surface recombination, friendliness to the environment, and stability. Last but not least, the perovskite materials’ design, which is mechanically layered, solves the problem of the absence of absorption losses, resulting in higher efficiency. In the beginning, the primary emphasis will be placed on finding ways to mitigate the problems that are inherent to thin film devices, such as poor absorption and high surface recombination.